Polygenic diseases - Sergey Dolomatov; Walery Zukow; Anna Zhukova; Svetlana Smirnova (Journal of Education, Health and Sport, 2025)
Background: Recent advances in molecular genetics have revolutionized our understanding of hereditary diseases, particularly polygenic (multifactorial) conditions. This comprehensive review examines the genetic basis of common polygenic diseases, including diabetes, preeclampsia, breast cancer, and factors influencing athletic performance.